Use of transmission error for a quantitative estimation of root-crack severity in gears. (15th May 2022) - Chin, Zhan Yie; Borghesani, Pietro; Mao, Yuanning; Smith, Wade A.; Randall, Robert B.
Highlights: Challenges of dynamic transmission error in gear crack severity assessment. Removal of transfer function, and separation of profile errors and deflections. Estimation of meshing compliance and geometric transmission error. Automated and accurate quantification of root-crack depth. Validation using encoder measurements from a spur gear rig. Abstract: Gear transmission error (TE) has been acknowledged as a prominent diagnostic tool in condition monitoring. Its advantages vs vibration include being closer to the source and less affected by transmission path effects. TE has recently demonstrated its enormous capabilities in gear wear severity assessment. For crack diagnostics, despite some promising preliminary results, a methodology for an accurate and reliable TE-based estimation of crack size was previously not available. In order to achieve this result two main obstacles needed to be overcome: (i) the removal of dynamic TE effects due to speed and (ii) the separation of profile error and compliance-related tooth deflections. This paper proposes a new crack-severity-estimation methodology that solves these problems. The proposed technique exploits different speeds and loads, often experienced by geared transmissions, and includes an automated identification of the cracked tooth and a crack-depth estimation based on a comparison with a theoretical tooth stiffness model. The proposed methodology is validated using experimental encoder measurements collected from a spur gear test rig with artificially seeded root cracks.